ECG and heart rate determination in fetal cattle using a digital signal processing method - Chen WenXi; Nemoto, T.; Kobayashi, T.; Saito, T.; Kasuya, E.; Honda, Y. (Wiley, 2002)
A method of recording the fetal electrocardiogram (ECG) and heart rate (HR) is described. An abdominal lead and a thoracic lead were used to measure the fetal ECG and maternal ECG, respectively. The maternal component in the abdominal lead measurement was estimated by a digital adaptive filter using the thoracic lead measurement as a reference. By suppressing the estimated maternal components in the abdominal lead, the fetal ECG could be detected. The beat-by-beat fetal QRS complex peaks were determined by a digital matched filter from the fetal ECG enhanced in this way. The method was tested on 10 pregnant Holstein cows at gestational periods ranging from 136 to 224 days. The results show that this method can extract the fetal ECG and determine the fetal HR from the raw noisy measurement data. The results suggest that the method would have applicability in monitoring fetal ECG as well as providing a non-invasive, continuous HR profile during gestation, which will enable better understanding of the development of cattle fetuses before delivery.